Effect on ruminal lactic acid utilization and lactic acid-utilizing bacteria - Miller, G.W.; Nagaraja, Tiruvoor G. (Kansas Agricultural Experiment Station, 2012)
The effect of diet on in vitro lactic acid utilization rate and counts of lactic add-utilizing bacteria was determined in ruminally cannulated steers. The steers were adapted to an alfalfa diet and gradually switched to an all-grain diet. The in vitro lactic acid fermentation rate increased with increased grain intake. Concurrently, the proportion of lactic acid-utilizing bacteria also increased. The increased population of lactic acid-utilizing bacteria is responsible for preventing lactic acid accumulation in the rumen of cattle adapted to consume a high-grain diet.
Keywords: Dairy; Ruminal lactic acid; Ruminal lactic acid bacteria; Feed intake